Soil Microbial Community Structure and Target Organisms under Different Fumigation Treatments - Sadikshya R. Dangi; James S. Gerik; Rebecca Tirado-Corbalá; Husein Ajwa (Applied and Environmental Soil Science)
Producers of several high-value crops in California rely heavily on soil fumigants to control key diseases, nematodes, and weeds. Fumigants with broad biocidal activity can affect both target and nontarget soil microorganisms. The ability of nontarget soil microorganisms to recover after fumigation treatment is critical because they play an important role in sustaining the health of agricultural and natural soil systems. Fumigation trial was conducted in Parlier, CA, and the study focuses on the effects of different rates of Telone C35 and also methyl bromide fumigation with polyethylene (PE) and totally impermeable film (TIF) tarps on target and nontarget soil microorganisms using field samples. Results indicated that the populations of target organisms, such as Fusarium oxysporum and Pythium spp., were reduced at all rates of fumigants. Phospholipid fatty acid (PLFA) analysis indicated that all major nontarget soil microbial groups such as Gram positive bacteria, Gram negative bacteria, fungi, and arbuscular mycorrhizal fungi (AMF) were affected by methyl bromide (MeBr) fumigation treatment. In general, the effects of Telone C35 (299 L/ha) under PE tarp had the least impact on microbial community structure and better effect on controlling target microorganisms and, therefore, indicated the better option among fumigation treatments.